Arctigenin Inhibits Liver Cancer Tumorigenesis by Inhibiting Gankyrin Expression via C/EBPα and PPARα - Sun, Ying; Tan, Yu-jun; Lu, Zhan-zhao; Li, Bing-bing; Sun, Cheng-hong; Li, Tao; Zhao, Li-li; Liu, Zhong; Zhang, Gui-min; Yao, Jing-chun; Li, Jie (Frontiers in Pharmacology, 2018)
Arctigenin (Arc), the component of Arctium lappa (burdock) which is the most popular daily edible vegetable in China and Japan because of its general health tonic effects, possesses multiple bioactivities in vivo and in vitro. To investigate the potential anti-tumor effects and probably mechanisms of Arc on liver cancer, two human hepatocellular carcinoma cell lines HepG2 and Hep3B were treated with series concentrations of Arc. The results showed that Arc-treatment inhibited HepG2 and Hep3Bcell growth (IC50 were 4.74 nM on HepG2 cells and 59.27 nM on Hep3B cells). In addition, migration, invasion, and colony formation of HepG2 cells were significantly inhibited by Arc (Inhibition ratios were 47.1%, 59.6%, and 60.5%, respectively). However, there were no differences in these parameters when Hep3B cells were treated by Arc. Furthermore, Arc also significantly inhibited the expression of gankyrin in both mRNA and protein levels in HepG2 cells (77% and 56% inhibition, respectively), but not in Hep3B cells. Luciferase assay identified that the target of Arc was from -450 to -400 of gankyrin promoter. Meanwhile, this region was the potential binding sites for both C/EBPα and PPARα, which were predicted and confirmed by online software and ChIP assay, simultaneously. Additionally, Co-immunoprecipitation (Co-IP) assay showed that in the presence of Arc, the binding between C/EBPα and PPARα was increased. However, Arc did not increase the expression of C/EBPα or PPARα. To identify the regulatory mechanism of Arc on gankyrin expression, binding screening assay and liquid chromatography-mass spectrometry (LC-MS) were performed. The results suggested that Arc could directly raise C/EBPα binding to gankyrin promoter (from -432 to -422), but not PPARα. Expressions of gankyrin, C/EBPα and PPARα in tumor tissues of patients were also detected by real-time PCR. C/EBPα and PPARα were both negatively correlated with gankyrin. In tumor bearing mice, Arc inhibited hepatocellular carcinoma growth significantly. In conclusion, all the results suggested that Arc inhibited liver cancer by directly recruiting C/EBPα to gankyrin promoter. PPARα further bound to C/EBPα, and both negatively regulated gankyrin expression. This study supplied a new mechanism for Arc against liver cancer.